2015
DOI: 10.1152/ajplung.00177.2015
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin E1 normalizes contractility, Ca2+ sensitivity and smooth muscle cell migration rate in TNF-α- and IL-6-pretreated human pulmonary arteries

Abstract: Pulmonary hypertension (PH) is a rare disease in which pathophysiology is characterized by an increase in proinflammatory mediators, chronic endothelial dysfunctions, and a high migration rate of smooth muscle cells (SMC). Over the course of the last decade, various treatments have been proposed to relax the pulmonary arteries, none of which have been effective in resolving PH. Our hypothesis is that artery-relaxing drugs are not the long-term solution, but rather the inhibition of tissue inflammation, which u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…Attenuation of VSMC migration by SPMs (ATL, RvD1, RvD2, RvE1, MaR1) has been a consistent finding in vitro , both with VSMC harvested from human saphenous veins (Ho, Spite et al 2010) (Miyahara, Runge et al 2013) and with arterial VSMC harvested from rodent aortas (Akagi, Chen et al 2015) (Petri, Laguna-Fernandez et al 2015, Wu, Mottola et al 2017) as well as human pulmonary arteries (Hiram, Rizcallah et al 2015). This effect has been demonstrated across several prototypic VSMC motogens including PDGF, thrombin, angiotensin II, TNF-α and IL-6 (Hiram, Rizcallah et al 2015, Mottola, Wu et al 2017, Wu, Mottola et al 2017). Associated with this effect, resolvins induce rapid and reversible changes in VSMC cell-shape with a decreased length:width ratio corresponding to an anti-migratory phenotype (Ho, Spite et al 2010, Miyahara, Runge et al 2013, Mottola, Wu et al 2017, Wu, Mottola et al 2017).…”
Section: Direct Effects Of Spm On Vascular Cellsmentioning
confidence: 60%
“…Attenuation of VSMC migration by SPMs (ATL, RvD1, RvD2, RvE1, MaR1) has been a consistent finding in vitro , both with VSMC harvested from human saphenous veins (Ho, Spite et al 2010) (Miyahara, Runge et al 2013) and with arterial VSMC harvested from rodent aortas (Akagi, Chen et al 2015) (Petri, Laguna-Fernandez et al 2015, Wu, Mottola et al 2017) as well as human pulmonary arteries (Hiram, Rizcallah et al 2015). This effect has been demonstrated across several prototypic VSMC motogens including PDGF, thrombin, angiotensin II, TNF-α and IL-6 (Hiram, Rizcallah et al 2015, Mottola, Wu et al 2017, Wu, Mottola et al 2017). Associated with this effect, resolvins induce rapid and reversible changes in VSMC cell-shape with a decreased length:width ratio corresponding to an anti-migratory phenotype (Ho, Spite et al 2010, Miyahara, Runge et al 2013, Mottola, Wu et al 2017, Wu, Mottola et al 2017).…”
Section: Direct Effects Of Spm On Vascular Cellsmentioning
confidence: 60%
“…In airway smooth muscle cells, it has been shown that TNF α increased [Ca 2+ ] i by modifying mitochondrial calcium concentration [38], decreasing the expression of Ca 2+ -ATPase, and slowing Ca 2+ reuptake [39]. Furthermore, it has been demonstrated that TNF α induced the upregulation of protein kinase pathways leading to an increment in Ca 2+ sensitivity [40]. Our results suggest that the increase in [Ca 2+ ] i observed after TNF α incubation could protect cells from a worse cilia slowing and the recovery of CBF to basal ciliary activity, after viscous loading.…”
Section: Discussionmentioning
confidence: 99%
“…MAG-DHA is neutral lipid which is very well absorbed by tissues [29] and becomes a DHA donor upon the action of MAG-lipase and the precursor of several omega-3 derivatives such as resolvins and protectins upon the action of 15-LOX and 5-LOX [10]. Resolvins have been reported to reduce pro-inflammatory markers [17,30], namely TNFα and IL-1β, and to prevent systemic hypertension in rats [31]. Furthermore, RvD1, A trihydroxylated DHA derivative has recently been reported to reverse the pharmacological reactivity and Ca 2+ sensitivity induced by ET-1 and IL-6 in human pulmonary artery [17].…”
Section: Discussionmentioning
confidence: 99%